Attempts of immunization of mice against experimental infection by Toxocara cati - Ilham Aed Asaad Al-Tikriti (Tikrit Journal of Pure Science)
studied the impact of muscular immunization to white mice (Balb / c) with serum and cell lymphoma of the spleen immunized mice with different antigens (mature eggs, live larvae, liquid hatch eggs, extract adult worm) of Toxocara canis to resist infection by the larvae of Toxocara cati in the case of hetero infection and against the larvae of Toxocara canis in similar infection case. The results showed that immunization with serum effect in reducing the rate of infection at the injection all different antigens (mature eggs, live larvae, liquid hatch eggs, extract adult worm)  reached as prevention ratio against T. cati 65.64%, 41.60%, 60.68%, 73.28% respectively, and the proportion of total prevention against T. canis with same antigens 71.90%, 51.83 %, 53.84%, 71.23% respectively. But when immunization lymphoma cell of the spleen mice immunized proportion to protect against T. cati it has reached 64.96%, 51.36%, 48.63%, 67.68%, respectively against antigens (mature eggs, live larvae, liquid hatch eggs, extract adult worm), and amounted to prevention ratio against T. canis 59.24%, 53.75%, 39.01%, 69.65% respectively in same infection.